Avaliação da validade, confiabilidade e responsividade da versão brasileira do Western Ontario Rotator Cuff Index - Lopes, Andréa Diniz [UNIFESP] (2008)
Objective: To evaluate the validity, reliability and responsiveness of the Brazilian Portuguese version of the WORC questionnaire. Methods: To test validity, 100 patients with rotator cuff disorders were evaluated using the WORC, clinically relevant outcomes for shoulder disorders (pain, range of motion and strength) and the DASH, SF-36 and UCLA outcome measures. The WORC was repeated on 50 patients on the same day and after a mean interval of 7 days to evaluate the testretest reliability. A sample of 30 patients were administered the WORC, DASH, UCLA and SF-36 scales again to asses the responsiveness at baseline and 3 months after a recommended treatment (physiotherapy or surgery) and were divided into 2 groups: those who had improved after treatment (n=20) and those who had not improved (n=10), according to anchor-based strategy. Concurrent validity was tested using Pearson’s correlation coefficient. Test-retest reliability and internal consistency were determined by the intraclass correlation coefficient and Cronbach’s alpha coefficient, respectively. The scores were used to assess the standard error measurement (SEM) and minimal detectable change (MDC). The effect size (ES) and standardized response mean (SRM) were calculated for responsiveness. Results: Analysis between the WORC and clinically relevant outcomes revealed weak to strong correlations; the weakest for active internal rotation (r=-0.22) and the strongest for pain during movement (r=-0.75). Strong correlations were found between the DASH and UCLA (r=-0.86 and r=-0.80, respectively). There were moderate correlations between the SF-36 domains (0.37 to 0.69); the best correlations related to the physical domains. Reliability analysis revealed excellent results, with the intraclass correlation coefficient and Cronbach’s alpha ranging from 0.88 to 0.99. The SEM was 5.2 and 3.0 for time 0 and after the interval of 7 days, respectively. The MDC was 7.1 over this mean time interval (90% confidence interval). Analyzing the responsiveness, all instruments showed larger ES and SRM values for those who “improved” than that found in the “not improved” group. The WORC demonstrated moderate to large ES and SRM values (0.66 to 1.1) for those “improved”. The same occurred for the ES and SRM values for the UCLA and DASH. The ES and SRM values of the SF-36 varied from small to large and the largest response was found in the physical role subscale. Conclusions: The Brazilian version of the WORC proved to be a valid and reliable measurement tool. The WORC as well as the UCLA, DASH and SF-36 physical subscales proved to be responsive for use in short-term follow-up after rotator cuff interventions.